Insect-Specific Flaviviruses Have Potential Applications as a Scaffold for Pathogenic Flavivirus Vaccines - Jia-Zhen Cui; Xiang-Hua Xiong; Qing-Yang Wang; Hao-Long Dong; Gang Liu; Hui-Peng Chen (Vaccines)
Pathogenic flaviviruses are predominantly the pathogens of emerging and re-emerging infectious diseases, which have caused multiple public health emergencies globally and pose a serious threat to human health and social development. Although significant achievements have been made in vaccine research, issues such as limited protective effects and virulence reversion persist, making the development of novel vaccines against pathogenic flaviviruses a current research hotspot and challenge. ISFVs have recently attracted attention due to their high homology with pathogenic flaviviruses and unique inability to replicate in mammalian hosts. Multiple vaccine candidate strains constructed using ISFVs as scaffolds have demonstrated excellent safety and efficacy. This review summarizes the biological characteristics, host restriction factors, current applications in vaccine development, and challenges faced by ISFVs, providing a reference for future research on pathogenic flavivirus vaccines.